Management and Outcomes of Clinical Scaphoid Fractures in Children. (May 2022) - Karir, Aneesh; Huynh, Minh N. Q.; Carsen, Sasha; Smit, Kevin; Cheung, Kevin
Background: Acute wrist trauma with clinical suspicion of a scaphoid fracture, but normal radiographs, is known as a clinical scaphoid fracture. Standard treatment involves immobilization and repeat radiographs in 10 to 14 days. When repeat radiographs are normal but a scaphoid fracture is still clinically suspected, the optimal management in children is unknown. This study retrospectively assessed the management and outcomes of pediatric patients diagnosed with clinical scaphoid fractures.Methods: A retrospective study was performed of all patients over a 2-year period treated for a clinical scaphoid fracture at a tertiary pediatric center. Patients were included if they had clinical signs of a scaphoid fracture and 2 negative x-rays 7 to 14 days apart postinjury.Results: Ninety-one patients with a mean age of 13.2 years (range: 7.8-17.7) were included. Sixteen patients (17.6%) underwent computed tomography (CT) or magnetic resonance imaging (MRI) at a mean time of 10.2 weeks postinjury. Five patients (5.5%) were diagnosed with a scaphoid fracture by x-ray or CT at an average of 4.5 weeks postinjury (range: 3-6). Six patients were diagnosed with other wrist fractures at a mean time postinjury of 3.1 (range: 3-6.5) weeks. Out of 195 total radiographs, the surgeon and radiologist disagreed on 59 (30.2%) images. No patients underwent surgery.Conclusions: Management of clinical scaphoid fractures at our institution was relatively uniform: nearly all patients were immobilized and less than 20% received advanced imaging. Our findings suggest a low but non-zero occult scaphoid fracture rate, discordance in radiologic interpretation, and lack of advanced imaging, providing an avenue for future prospective studies.